New Criteria for Meromorphic Starlikeness and Close-to-Convexity - Ali Ebadian; Nak Eun Cho; Ebrahim Analouei Adegani; Sibel Yalçın (Mathematics, 2020)
The main purpose of current paper is to obtain some new criteria for meromorphic strongly starlike functions of order <semantics> α </semantics> and strongly close-to-convexity of order <semantics> α </semantics> . Furthermore, the main results presented here are compared with the previous outcomes obtained in this area.